Surface Behaviors of Pine Wood (Pinus nigra) After Short-Term Weathering: Urban Furniture Suitability Investigation - Sahin, Candan Kus; Merdan, Rahim (European Journal of Applied Sciences, 2025)
The tangential/radial ratio (T/R) has usually been used to investigate wood’s physical properties due to moisture uptake and loss differences. In this issue, the color coordinate differences were evaluated between two surfaces for Black pine (Pinus nigra). Initially (controls), it was measured to be a (T-R)L*: 10.71 1.45 (metric) difference for lightness, (T-R)a*: -0.07 (metric) for a* coordinate, and (T-R)b*:- 0.14 (metric) for the b* coordinates. However, the total color changes (discoloration) of two surfaces were found to be after outdoor exposure, separately. The tangent surface shows ΔET: 10.71 (metric), which is higher than the radial surface values of ΔER: 8.57 (metric) after weathering. The chroma and hue differences were observed to be negligible for control and weathered samples, with only <2.0 units differences for both surfaces. A similar trend was also observed for gloss properties: all gloss differences were found to be <3.0 Gu which could not be visually differentiated easily. The radial surface seemed to have a higher yellowness value than tangent surfaces, which was found to be YIR: 52.70 (numeric) for radial surfaces and YIT: 47.62 (numeric) for tangent surfaces. After weathering, considerably lower X-(red), Y-(yellow) and Z-(blue) stimuli values were calculated: ΔXT(w-c):-12.68 (numeric) in tangent and ΔXR(w-c): -10.67 (numeric) in radial surface for X stimuli, ΔYT(w-c): -12.47 (numeric) in tangent- and ΔXR(w-c): -10.46 (numeric) in radial surface for Y stimuli; and ΔZT(w-c): -7.28 (numeric) for tangent and ΔZR(w-c): -7.42 (numeric) in radial surface for Z stimuli, respectively.